Long-range recruitment of Martinotti cells causes surround suppression and promotes saliency in an attractor network model - Krishnamurthy, Pradeep; Silberberg, Gilad; Lansner, Anders (Frontiers in Neural Circuits, 2015)
Although the importance of long-range connections for cortical information processing has been acknowledged for a long time, most studies focused on the long-range interactions between excitatory cortical neurons. Inhibitory interneurons play an important role in cortical computation and have thus far been studied mainly with respect to their local synaptic interactions within the cortical microcircuitry. A recent study showed that long-range excitatory connections onto Martinotti cells mediate surround suppression. Here we have extended our previously reported attractor network of pyramidal and Martinotti cells by introducing long-range connections targeting Martinotti cells. We have demonstrated how the network with Martinotti cell-mediated long-range inhibition gives rise to surround suppression and also promotes saliency of locations at which simple non-uniformities in the stimulus field are introduced. Furthermore, our analysis suggests that the presynaptic dynamics of Martinotti cells is only ancillary to its orientation tuning property in enabling the network with saliency detection. Lastly, we have also implemented a disinhibitory pathway mediated by another interneuron type (VIP interneurons), which inhibits Martinotti cells and abolishes surround suppression.